Implementation of Investigation into School Uniform Corruption Crime - Firdaus, Sarah; Sukmareni, Sukmareni (Faculty of Law, Universitas Pattimura, 2025)
Introduction: The perpetrators of corruption crimes are difficult to detect and organized by one person, the Payakumbuh District Attorney's Office, which handles the case, being one of the institutions assigned to handle this case. An ideal and balanced solution is needed to address this crime, which may be considered a national problem.Purposes of the Research: Examining the implementation, factors and obstacles that occur in the crime of corruption of elementary and junior high school uniforms within the Education Office (Disdik) of Fifty Cities Regency at the Payakumbuh District Attorney's Office.Methods of the Research: This research utilizes an empirical juridical research strategy, which is an approach to studying law with a focus on the direct application of legal rules that apply to various legal events that occur in society.Findings of the Research: The implementation of investigations into corruption cases at the Payakumbuh District Attorney's Office, prosecutors face several obstacles, to overcome these obstacles strategic efforts are needed, with these efforts, especially at the Payakumbuh District Attorney's Office, can take place faster, transparently, and in accordance with the principles of justice, as well as regrow public trust in law enforcement, with the aim of enforcing the law, restoring state finances, and providing a deterrent effect for perpetrators corruption.